Investigation of frequency responses of a sandwich beam on the base of viscous model of damping - Vorob'ev, С. А. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
Equations of motion of a sandwich elastic beam with taking into account internal damping in materials of layers on the base of Voigt model are given. Methods of Fourier and complex amplitudes are used in analysis of free and stationary forced vibrations. Spectrums of fundamental frequencies of ideal and damped sandwich beams were examined, comparative analysis was given. Amplitude and phase-frequency responses were obtained. Conclusion about incorrectness of viscous model of damping in the problem of investigation of free and forced vibrations of a sandwich beam was done.